Primary afferent nociceptors - Handwerker, Hermann (Henry Stewart Talks, 2009)
Nociceptors are the peripheral neurons subserving pain, History of the concept, Characterization of cellular mechanisms, Plasticity as basis of clinical pain states, Membrane receptors as basis of pain therapies, Nociceptors in humans